(untitled) - Alice Oshima (Tp. HCM, 1997)
The book is divided into four parts: Writing a paragraph, W. riting an Essay, Using Outside References, and Sentence Structure. The appendixes provide a review of punctuation rules, a chart of transition signals, and a summary of verb forms
Keywords: english language - sentences,english language - study and teaching